Cell Wall Enzymes in Zygnema circumcarinatum UTEX 1559 Respond to Osmotic Stress in a Plant-Like Fashion - Fitzek, Elisabeth; Orton, Lauren; Entwistle, Sarah; Grayburn, W. Scott; Ausland, Catherine; Duvall, Melvin R.; Yin, Yanbin (Frontiers in Plant Science, 2019)
Previous analysis of charophyte green algal (CGA) genomes and transcriptomes for specific protein families revealed that numerous land plant characteristics had already evolved in CGA. In this study, we have sequenced and assembled the transcriptome of Zygnema circumcarinatum UTEX 1559, and combined its predicted protein sequences with those of 13 additional species [five embryophytes (Emb), eight charophytes (Cha), and two chlorophytes (Chl) as the outgroup] for a comprehensive comparative genomics analysis. In total 25,485 orthologous gene clusters (OGCs, equivalent to protein families) of the 14 species were classified into nine OGC groups. For example, the Cha+Emb group contains 4,174 OGCs found in both Cha and Emb but not Chl species, representing protein families that have evolved in the common ancestor of Cha and Emb. Different OGC groups were subjected to a Gene Ontology (GO) enrichment analysis with the Chl+Cha+Emb group (including 5,031 OGCs found in Chl and Cha and Emb) as the control. Interestingly, nine of the 20 top enriched GO terms in the Cha+Emb group are cell wall-related, such as biological processes involving celluloses, pectins, lignins, and xyloglucans. Furthermore, three glycosyltransferase families (GT2, 8, 43) were selected for in-depth phylogenetic analyses, which confirmed their presence in UTEX 1559. More importantly, of different CGA groups, only Zygnematophyceae has land plant cellulose synthase (CesA) orthologs, while other charophyte CesAs form a CGA-specific CesA-like (Csl) subfamily (likely also carries cellulose synthesis activity). Quantitative real-time-PCR experiments were performed on selected GT family genes in UTEX 1559. After osmotic stress treatment, significantly elevated expression was found for GT2 family genes ZcCesA, ZcCslC and ZcCslA-like (possibly mannan and xyloglucan synthases, respectively), as well as for GT8 family genes (possibly pectin synthases). All these suggest that the UTEX 1559 cell wall polysaccharide synthesis-related genes respond to osmotic stress in a manner that is similar to land plants.